Análise do efeito de inseticidas neonicotinóides sobre a orientação e coleta de alimento de operárias de Apis mellifera L., 1758 (Hymenoptera: Apidae) - Nominato, Fellipe Chaves [UNESP] (2015)
The Apis mellifera bees has its great importance as one of the most economically valuable pollinators for crops worldwide, ensuring cross-pollination and increasing fruit yield. On the other hand, increasingly more agricultural chemicals developed in order to control weeds, fungi and insect pests to ensure productivity. Insecticides are used on a large scale in the state of São Paulo, in citrus crops to control huanglongbing (HLB) and sugar cane for the control various pests. Applications are usually made by aircraft and as a result a significant mortality is observed in apiaries near the plantations. Honey bees can come into contact with such chemical agente through their collection of water activities, plant resins, pollen and néctar. The resulting poisoning of this exposure can be lethal, which is readily detectable or cause effects on the physiology and insect behavior. These effects, which in turn are hardly detectable, can be palsy, disorientation or behavioral changes; but can compromisse the entire social structure of the colony. For this reason the objectives of this project were to study the bee orientation capacity A. mellifera and the effects of thiamethoxam and acetamiprid insecticide via topical application using the experimental model of the maze, which reproduces the foraging activities in the field. It was observed that sublethal doses (LD50/100, LD50/10 and LD50) of thiamethoxam and acetamiprid insecticides, applied topically, have caused deleterious effects in the maze tests. For thiamethoxam, there was an increase in flight times and food collection and worse performance for the three doses in compared to control group. For acetamiprid, there was an increase in flight times and food collection, worse performance and lower amount of food collected for the three doses in compared to control group. The method of analysis of the flight behavior and food collection employee, can be directly related to the activity of bees ...